Optimalisasi Manajemen Lalu Lintas Kawasan Jenderal Sudirman Kota Salatiga - Rahadian Pradipta; Bambang Haryadi; Ismiyati Ismiyati (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
The Jenderal Sudirman area has a strategic function as a trade and service area that gives strong character in the Salatiga. The growth of trade and service activities has increased to become a regional trading area that is influenced by modern trade. With the existence of modern shopping centers, five-star hotels, banking services beside the existing traditional markets affect the increasement of activities. The high intensity of activities raises problems related to traffic congestion. The purpose of this research is to determine the performance of the road network in the Jenderal Sudirman area and formulate a traffic management strategy to deal with the current traffic problems. This research was conducted by analyzing the existing conditions. The method of calculating volume, degree of saturation, and speed used is MKJI 1997. This study uses the SATURN 10.4 program to determine overall network performance. The results showed that the existing condition of the Jenderal Sudirman area undergone problems in Jalan Jenderal Sudirman (2 directions) with 0.86 degree of saturation. The first scenario analysis shows the value of the degree of saturation in Jalan Jenderal Sudirman dropped to 0.55; The Second scenario analysis to 0.90; and the third scenario analysis becomes 0.98. As for the overall network performance, first scenario has advantages on 3 indicators, namely average speed, passenger car unit(pcu)-hour, pcu-rupiah. Based on the overall analysis, a concept of handling traffic problems can be arranged by applying the traffic management strategy first scenario and second scenario through the short-term and long-term stages.